We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
260
1
avatar+156 

I'm not sure if I am correct on these. Please check? Thank you!

 Aug 17, 2018

Best Answer 

 #1
avatar+7616 
+3

I think all your answers are correct! laughlaugh👍

I got the same answer for each one:

 

k(m)  =  m2 - 7m - 18

k(m)  =  (m - 9)(m + 2)

The zeros are the values of  m  that make  k(m)  equal zero, so the zeros are  9  and  -2 .

C)  One positive zero and one negative zero, where the positive zero has the larger absolute value

 

f(x)  =  2x2 - 11x + 12

f(x)  =  2x2 - 8x - 3x + 12

f(x)  =  2x(x - 4) - 3(x - 4)

f(x)  =  (x - 4)(2x - 3)

The zeros are  4  and  3/2  .

D)  Two positive zeros

 

s(r)  =  5r2 + 49r - 10

s(r)  =  5r2 + 50r - 1r - 10

s(r)  =  5r(r + 10) - 1(r + 10)

s(r)  =  (r + 10)(5r - 1)

The zeros are  -10  and  1/5 .

F)  One positive zero and one negative zero, where the negative zero has the larger absolute value

 

z(w)  =  w2 + 7w + 6

z(w)  =  (w + 6)(w + 1)

The zeros are  -6  and  -1 .

E)  Two negative zeros

 Aug 17, 2018
 #1
avatar+7616 
+3
Best Answer

I think all your answers are correct! laughlaugh👍

I got the same answer for each one:

 

k(m)  =  m2 - 7m - 18

k(m)  =  (m - 9)(m + 2)

The zeros are the values of  m  that make  k(m)  equal zero, so the zeros are  9  and  -2 .

C)  One positive zero and one negative zero, where the positive zero has the larger absolute value

 

f(x)  =  2x2 - 11x + 12

f(x)  =  2x2 - 8x - 3x + 12

f(x)  =  2x(x - 4) - 3(x - 4)

f(x)  =  (x - 4)(2x - 3)

The zeros are  4  and  3/2  .

D)  Two positive zeros

 

s(r)  =  5r2 + 49r - 10

s(r)  =  5r2 + 50r - 1r - 10

s(r)  =  5r(r + 10) - 1(r + 10)

s(r)  =  (r + 10)(5r - 1)

The zeros are  -10  and  1/5 .

F)  One positive zero and one negative zero, where the negative zero has the larger absolute value

 

z(w)  =  w2 + 7w + 6

z(w)  =  (w + 6)(w + 1)

The zeros are  -6  and  -1 .

E)  Two negative zeros

hectictar Aug 17, 2018

5 Online Users

avatar